Induction of fetal hemoglobin: Lentiviral shRNA knockdown of HBS1L in β0thalassemia/HbE erythroid cells - Chumchuen S. (2023)
Imbalanced globin chain output contributes to thalassemia pathophysiology. Hence, induction of fetal hemoglobin in β-thalassemia and other β-hemoglobinopathies are of continuing interest for therapeutic approaches. Genome-wide association studies have identified three common genetic loci: namely β-globin (HBB), an intergenic region between MYB and HBS1L, and BCL11A underlying quantitative fetal hemoglobin production. Here, we report that knockdown of HBS1L (all known variants) using shRNA in early erythroblast obtained from β0-thalassemia/HbE patients triggers an upregulation of γ-globin mRNA 1.69 folds. There is modest perturbation of red cell differentiation assessed by flow cytometry and morphology studies. The levels of α- and β-globin mRNAs are relatively unaltered. Knockdown of HBS1L also increases the percentage of fetal hemoglobin around 16.7 folds when compared to non-targeting shRNA. Targeting HBS1L is attractive because of the potent induction of fetal hemoglobin and the modest effect on cell differentiation.